Osoby z niepełnosprawnością w dobie pandemii – perspektywa kanadyjska - Skalska, Katarzyna (Życie z niepełnosprawnością w świecie VUCA, 2022)
The article is an attempt to analyze the situation of people with disabilities in Canada during the pandemic, and at the same time an incentive to find good practices inspiring to implement solutions promoting the social activity of people with disabilities. At the outset, the author describes in general the specific social conditions that are associated with this country. The considerations are based on the biopsychosocial model of disability, which provides a conceptual framework for the presentation of Canadian research regarding people with disabilities.